Student evaluation of teachers' work in project-based teaching in higher vocational education - Mijić, Miloš (E-business technologies conference proceedings, 2025)
Teachers in higher vocational education should often critically review their teaching work. In addition to self-examination, it would be desirable to include students in their critical analysis. Feedback from students can greatly help the teacher to critically examine aspects of their work and then make an effort to improve them. The paper has designed and tested a method of collecting feedback for the teacher from students for one segment of the implemented project teaching. Through a survey, information about the teacher's work was collected, such as ratings that show students' satisfaction with the teacher's organizational skills and his willingness to help in critical situations. The students' opinion of the teacher represents important feedback that they will use to analyze their own work. After critically reviewing the analyzed information, the teacher can correct his work in order to build his own approach to teaching practice, creating his own professional identity and his own system of teaching values ​​with significant credibility among his students.